HYBRIDITY OF SABINE KUEGLER’S IDENTITY IN HER AUTOBIOGRAPHY, JUNGLE CHILD - Andina Meutia Hawa; Dyani Prades Pratiwi; Fakhria Nesa (Linguistics and Literature Students' Journal, 2023)
Sabine Kuegler is a German author who was born in Nepal. In her autobiography, Jungle Child, she shared her life experience living in a Papuan jungle as a child.She was accustomed to living a simple life that was untouched by modernization, among the Fayu people, a newly discovered tribe in Foida, West Papua. At the age of 17 she moved back to Germany by herself and found it difficult adjusting to her new environment. This was mainly caused of her deep-rooted connection to Papua culture and her lack of knowledge about European culture. This study aims to reveal the form of the appearance of hybridity, liminality, and ambivalence in Sabine's identity. This paper uses a qualitative method which is in line with postcolonialism discourse. Bhabha (1994)suggest that hybridity is a cross between cultures in society, which appears in various forms, such as language and manner. The result shows that the process of reforming her subjectivity is shown through symbolizations such as place and time setting which at fist creates dichotomies such as East vs West, and childhood vs adulthood. However, Sabine managed to find the connection between those dichotomies, which led to acceptance of her hybrid identity as a German who will always be a part of the jungle. The ambivalence of her identity is shown through her interaction as a German kid with Fayu People and her constant attempt to integrate into Western culture which always brings her back to her life in the jungle.Keywords: ambivalence, autobiography, hybridity, identity, postcolonialism